The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/etc.29
|View full text |Cite
|
Sign up to set email alerts
|

Observed and predicted reproduction of Ceriodaphnia dubia exposed to chloride, sulfate, and bicarbonate

Abstract: Chronic toxicities of Cl(-), SO(4) (2-), and HCO(3) (-) to Ceriodaphnia dubia were evaluated in low- and moderate-hardness waters using a three-brood reproduction test method. Toxicity tests of anion mixtures were used to determine interaction effects and to produce models predicting C. dubia reproduction. Effluents diluted with low- and moderate-hardness waters were tested with animals acclimated to low- and moderate-hardness conditions to evaluate the models and to assess the effects of hardness and acclimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…Results of the 129 toxicity tests described herein are consistent with available literature concerning toxicity of sulfate-dominated mining effluents [34], simulated mining effluents [35] and sulfate toxicity [19, 20]. Kunz and others [36] reported the chronic toxicity of reconstituted waters simulating alkaline mine discharges to C .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Results of the 129 toxicity tests described herein are consistent with available literature concerning toxicity of sulfate-dominated mining effluents [34], simulated mining effluents [35] and sulfate toxicity [19, 20]. Kunz and others [36] reported the chronic toxicity of reconstituted waters simulating alkaline mine discharges to C .…”
Section: Discussionsupporting
confidence: 87%
“…The ability of hardness to mitigate toxicity was reduced in the 320 mg/l CaCO3 treatment of the study with NOEC/LOECs for sulfate exposure lower at the highest hardness concentration. Lasier and Hardin [20] reported NOEC/LOEC concentration values of 1000/1250 mg/l sulfate in water with moderate-hardness and moderate alkalinity. In testing of a saline mine discharge with the cladoceran, Moinodapnia macleayi , van Dam and others [37] found reproductive impairment evident at 1500 μS/cm in a sodium sulfate test solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally speaking, EC50/IC50 values from these studies were within or only marginally beyond the intertest variability observed in the present study at 0.36 mM Ca. Lasier and Hardin (2010) tested the toxicity of NaCl, Na 2 SO 4 , and NaHCO 3 in each of 3 dilution waters with varying Ca and alkalinity. Lasier and Hardin (2010) tested the toxicity of NaCl, Na 2 SO 4 , and NaHCO 3 in each of 3 dilution waters with varying Ca and alkalinity.…”
Section: Models Based On Concentrationmentioning
confidence: 99%